PENGEMBANGAN MESIN PUNCHER SCREENY FLEXO DENGAN METODE QUALITY FUNCTION DEPLOYMENT - Oase Fattan Rabbani; Zulkarnain Zulkarnain; Emmidia Djonaedi (Lembaga Pengembangan Kinerja Dosen, 2025)
In the printing process, PT XYZ still experiences several obstacles that affect the final result of the mold. One of them is the difficulty in equalizing the position of the screen and plate which causes register inaccuracy, as well as problems in the process of cutting the screen by the prepress operator. This research aims to make recommendations for the development of the Flexo Screen Puncher machine to overcome these problems. The method used is Quality Function Deployment (QFD) to identify user needs and translate them into appropriate technical responses. Based on the results of expert validation, the efficiency of the screen cutting process is the highest Voice of Customer (VoC) with an importance weight of 0.22. Meanwhile, the technical response with the highest Technical Importance value was obtained by the addition of visual management with a scale of 25%. This result indicates that every work process must be clearly visualized through visual management in order to minimize existing problems.